Problems and ways of translating the information on the signs of cities in Kazakhstan (on the example of the city of Turkistan) - Kim, A.; Ryskeldinova, L.; Serikov, A.; Yesbatyrova, Zh. (Submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts In Translation Studies M. S. Narikbayev KAZGUU University School of Liberal Arts, 2021)
The absence of translation or mistranslation of the information on the public signs in the city of Turkistan is a crucial problem. Research has shown that the problem with translation can negatively affect the tourists’ experience. This paper aims to identify the common mistakes in the translation of public signs in the Turkistan city, determine the impact on tourists, and suggest the right ways to adapt the solution to the problem. To investigate the problem, the signs in the city were analyzed to categorize their mistakes; online and offline surveys and interviews were conducted with people connected to tourism. Analysis of the responses demonstrated that problems with translation complicate the navigation through the city. The paper suggests ways to avoid the problems with the misunderstanding of signs. The research work contributes to decreasing translation mistakes and improving tourism from the signs’ aspect.
Keywords: translation; signs; tourist; mistakes